Crime, deterrence and unemployment in Greece: a panel data approach - George Saridakis; Hannes Spengler (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This study empirically examines the relationship between crime, deterrence and unemployment in Greece. A regional dataset over the period 1991-1998 was collected and analyzed. Our econometric methodology follows the Generalized Method of Moments (GMM) estimator applied to dynamic models of panel data. The results show that property crimes are significantly deterred by higher clear-up rates. Also for property crime rates, the results indicate that unemployment increases crime. For violent crimes, however, the effect of the clear-up rate and unemployment are found to be insignificant.
Keywords: 330; Crime; deterrence; unemployment; panel data; GMM; Kriminalität; Kriminalpolitik; Arbeitslosigkeit; Regionale Arbeitslosigkeit; Panel; Griechenland